Effectiveness of Endorphin Massage for Breast Milk Production to Postpartum Mothers Caesarea Section - Aini, Qurrotu; Suryaningsih , Merlyna; Mufarika, Mufarika (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Especially if the mother receives general anesthetic during the delivery procedure Sectio Caesarea (SC), the mother frequently isn't able to breastfeed the newborn in the first few hours after birth. The process of breastfeeding is slightly impeded by the state of the abdominal surgery wound. According to the early study's findings, 1 nursing respondent was fluent whereas 4 breastfeeding respondents did not come out of the closet. Therefore, it can be said that certain SC postpartum mothers still have erratic milk production. This study compared the smoothness of milk produced by postpartum SC women after receiving back massages and endorphin massages. Quasy Experiment pretest posttest design group is the study methodology used. The dependent variable is the smoothness of breast milk production, while the independent variable is endorphin massage. There are 17 respondents in the general population, and 10 postpartum SC mothers were selected as samples. The research instrument is an observation sheet, and the sample method is incidental sampling. Wilcoxon test statistical analysis with (0.05). The ethical viability of this study has been evaluated by KEPK RSUD dr. Mohammad Zyn Sampang No.445/561/434.203.100/2022. With a p-value of 0.0083 0.05, the Wilcoxon test results from the study revealed that there were changes in the smoothness of milk production before and after receiving an endorphin massage. Teaching back massage techniques and endorphin massage as an extra therapy to boost the smooth production of breast milk is believed to help health professionals provide better services regarding the production of breast milk without interruption.